Influence of chromium on the phase composition and specific features of hardening of the MnFeCoNiCu high-entropy alloy - О. Myslyvchenko; Мисливченко О.; М. Krapivka; Крапівка М.; О. Tereshchenko; Терещенко О.; Filep Mykhailo; Філеп Михайло; Filep Mihály (My University, 2020)
Abstract. A six-component system of CoNiCuCrx high-entropy alloys with different contents of chromium (where x = 0, 0.5, 1.0, 2.0, and 3.0 mole) is obtained by the method of argon-arc melting in a МІFІ-9 study. By the methods of X-ray diffraction analysis, scanning-electron microscopy, and indentation, we investigate the influence of chromium on the crystalline structure, microstructure, and hardness of these alloys in the as-cast state. In their structure, depending on the chromium content, we detect a mixture of the following phase components: two face-centered cubes + a body-centered cube + an intermetallic σ -phase (FCC1 + FCC2 + BCC + σ ). It is also established that, as the chromium content increases, we observe the formation of the bcc structure and the σ -phase, which is the predominant factor of hardening of the alloy.
Contents: https://link.springer.com/journal/11003/volumes-and-issues/56-3 Editorial board: https://link.springer.com/journal/11003/editors
Keywords: high-entropy alloys; phase composition; hardness